PRODUCTIVITY COEFFICIENT – KY OF CARIOCA BEAN (Phaseolus vulgaris L. TAA DAMA.) FOR THE MUNICIPALITY OF BOTUCATU-SP - dos Santos, Rafaela Magalhães [UNESP]; Román, Rodrigo Máximo Sánchez [UNESP]; Filho, Helio Grassi [UNESP]; da Silva, Vicente Mota [UNESP]; Pereira, Anderson de Jesus [UNESP] (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2022)
The irrigation presents itself as a fundamental tool for water security in agriculture. Studies on the rational irrigation water use are of importance for a good productivity, while at the same time ensuring water and power costs. In this sense, a determination of water response coefficients (Ky) appears as an alternative to carry out irrigation management. The objective of this work was to determine the Ky values for different bean phenological phases. An experiment was installed in a greenhouse, the experimental design was in a completely randomized design, consisting of 4 treatments and 12 repetitions. The treatments were application of water deficit, a different phenological stages: T1: control (there was no water up to deficit at any time); T2: vegetative stage; T3: flowering stage; T4: grain filling stage. It was measured the productivity. The collected data had an analysis of variation and Tukey test at 5% probability. It was possible to conclude that the grain filling stage, at 82 days after sowing, was the phase that obtained the greatest loss of productivity, resulting in a 52.2% decrease in productivity compared to the control. Thus, Ky values in the vegetative, flowering and grain filling stages were 1.37, 1.69 and 1.85 respectively.
COEFICIENTE DE PRODUTIVIDADE – KY DO FEIJÃO CARIOCA (Phaseolus vulgaris L. TAA DAMA.) PARA O MUNICÍPIO DE BOTUCATU-SP
Keywords: evapotranspiration; Hargreaves Samani; tensiometer; water response coefficient (Ky)